Free fatty acid receptors - Milligan, Graeme; Kimura, Ikuo (Handbook of experimental pharmacology ;, 2017)
"This book highlights the important role free fatty acids (FFA) play as potential drug targets. While FFA have long been considered byproducts of cell metabolism, they are now recognized as ligands that regulate cell and tissue function via G-protein-coupled receptors. At least three receptors have been identified for which FFA appear to be the endogenous ligands"--Publisher's description.